Evolution of Scientific Efforts to Define Cystometric Bladder Morphology in Neurogenic Bladder: A Narrated Review - Arvind Sinha; Shrilakshmi Aithal (Journal of Indian Association of Pediatric Surgeons)
Children with high-pressure bladders are at an increased risk of upper tract deterioration, potentially leading to chronic renal failure if not adequately managed. Regular bladder pressure monitoring is essential, especially in patients with neurogenic bladders, often resulting from spinal dysraphism. Urodynamic studies (UDSs) are the gold standard for assessing bladder pressure but are invasive, resource-intensive, and uncomfortable for patients. Over the last many decades, there have been regular attempts to characterize the morphology of the neurogenic bladder, including the classical subjective appearance of the “Christmas Tree” bladder, to objectively define the shape of the bladder via the use of height-to-width ratio. The study explores the evolution of scientific efforts to define bladder morphology in neurogenic bladder and to describe the current state of evidence regarding the correlation of the shape of the bladder with the detrusor pressures and upper tract changes in children with neurogenic bladder.